PROGRAM CORPORAT SOCIAL RESPONSIBILITY PT CARGILL DALAM PENGEMBANGAN KAPASITAS ANAK DAN MENINGKATKAN MINAT BACA MELALUI â€œBOOKS FOR KIDSâ€ - Qonaâ€™ah, Siti (Universitas Bina Sarana Informatika, 2016)
â€œBooks For Kidsâ€ program in Capacity building and improving childrenâ€™s in reading is a part of corporat social responsibility conducted by PT Cargill since 2011. Corporat social responsibility program in the field of education, in 2016 carried out by giving the 1100 books at SDN 1 Godong Grobogan,Â central Java. Â This research is to find out the corporat social responsibility program PT Cargill in developing the capacity of children and improve the studends reading interest through books for kids SDN 1 Godong Grobogan, Central Java.In this study researchers used a qualitative approach and case studies, as method of research that suggest that through books for kids are part of corporat social responsibility program in the field of education. Thus theÂ corporate Social responsibilityÂ program through books for kids can develop the capacity of children and improve the students reading Â interest SDN 1 Godong Grobogan District, Central JavaÂ Keywords: Corporate Social Responsibility, Capacity Building, Interest in reading